Dysregulated arginine metabolism and cardiopulmonary dysfunction in patients with thalassaemia. (24th April 2015) - Morris, Claudia R.; Kim, Hae‐Young; Klings, Elizabeth S.; Wood, John; Porter, John B.; Trachtenberg, Felicia; Sweeters, Nancy; Olivieri, Nancy F.; Kwiatkowski, Janet L.; Virzi, Lisa; Hassell, Kathryn; Taher, Ali; et al.
Summary Pulmonary hypertension (PH) commonly develops in thalassaemia syndromes, but is poorly characterized. The goal of this study was to provide a comprehensive description of the cardiopulmonary and biological profile of patients with thalassaemia at risk for PH. A case–control study of thalassaemia patients at high versus low PH‐risk was performed. A single cross‐sectional measurement for variables reflecting cardiopulmonary status and biological pathophysiology were obtained, including Doppler‐echocardiography, 6‐min‐walk‐test, Borg Dyspnoea Score, New York Heart Association functional class, cardiac magnetic resonance imaging (MRI), chest‐computerized tomography, pulmonary function testing and laboratory analyses targeting mechanisms of coagulation, inflammation, haemolysis, adhesion and the arginine‐nitric oxide pathway. Twenty‐seven thalassaemia patients were evaluated, 14 with an elevated tricuspid‐regurgitant‐jet‐velocity (TRV) ≥ 2·5 m/s. Patients with increased TRV had a higher frequency of splenectomy, and significantly larger right atrial size, left atrial volume and left septal‐wall thickness on echocardiography and/or MRI, with elevated biomarkers of abnormal coagulation, lactate dehydrogenase (LDH) levels and arginase concentration, and lower arginine‐bioavailability compared to low‐risk patients. Arginase concentration correlated significantly to several echocardiography/MRI parameters of cardiovascular function in addition to global‐arginine‐bioavailability and biomarkers of haemolytic rate, including LDH, haemoglobin and bilirubin. Thalassaemia patients with a TRV ≥ 2·5 m/s have additional echocardiography and cardiac‐MRI parameters suggestive of right and left‐sided cardiac dysfunction. In addition, low arginine bioavailability may contribute to cardiopulmonary dysfunction in β‐thalassaemia.